Experimental comparison between steam and water tilt-angle injection effects on NOx reduction from the gaseous flame. Issue 41 (23rd July 2021) - Kotob, Mostafa Raafat; Lu, Tianfeng; Wahid, Seddik S.
Abstract : We experimentally compare the effect of different direct water and steam injection tilting angles on NOx emission values. The results showed that water and steam injection are effective tools to reduce NOx emission by 70% and 57% respectively. Abstract : Nitrogen oxide emissions control is a technology that meets the air pollutant reduction criteria in the energy production field, and it becomes more stringent yearly. Thus, this study experimentally compares the effects of direct-water and -steam injections at different tilting angles on NOx emission reduction. Using the experimental study conducted in the Combustion Laboratory of the Mechanical Power Department at the Faculty of Engineering, Minia University, Egypt, the exhaust gas temperature was found to be the main parameter affecting NOx emission. An experimental test rig was designed and simulated as a gaseous fuel combustion chamber. The results show that water and steam injections can effectively reduce NOx emissions by 70% and 57%, respectively. Besides, direct-water injection is more effective than steam injection owing to the 13% extra reduction in the NOx emission. Moreover, the best inclination angle into the primary combustion zone for both water and steam injection is 45°. The experimental results agree well with the results obtained in previous studies in this field.